(untitled) (Journal of Oriental Studies, 2025)
The meeting held in Davos in 1988 between Greek Prime Minister Andreas Papandreou and Turkish Prime Minister Turgut Özal aimed to alleviate the long-standing tensions between the two countries. Its goal was to promote dialogue and reduce the likelihood of military and diplomatic clashes. Although initial optimism was evident, it quickly dissipated due to unresolved contradictions and deeply rooted historical issues. The Cyprus issue, minority rights, and disagreements over military balance in the Aegean Sea persisted, fueled by years of accumulated mistrust. Ultimately, the Davos process did not live up to expectations and is seen as a missed opportunity to overcome the historical burden.